CSC555: Software Engineering / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics And Media (Universiti Teknologi MARA (UiTM), 2022)
The subject provides an introduction to the discipline of Software Engineering. The emphasis is upon a broad coverage of the areas, since students will at this early stage not have adequate programming skills to tackle many of the topics in greater depth. The notion of a software system as a model or approximation of a desired system is introduced, and used as a way of describing such things as the software life cycle and its various models, programming by contract, design and testing issues, maintenance, reuse, project management and software legacy. Upon successful completion of the module, students will have demonstrated knowledge of the strengths and weaknesses of the software development life cycle and the ability to practice software engineering techniques for a given problem. Apply and reflect upon project management techniques used to solve a given problem.